2020
DOI: 10.1002/jor.24750
|View full text |Cite
|
Sign up to set email alerts
|

New materials for hip and knee joint replacement: What's hip and what's in kneed?

Abstract: Over the last three decades there have been significant advancements in the knee and hip replacement technology that has been driven by an issue in the past concerning adverse local tissue reactions, aseptic and septic loosening. The implants and the materials we utilize have improved over the last two decades and in knee and hip replacement there has been a decrease in the failures attributed to wear and osteolysis. Despite these advancements there are still issues with patient satisfaction and early revision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 83 publications
(146 reference statements)
0
23
0
Order By: Relevance
“…However, understanding the reactivity of wear particles released from CoCrMo components in relation to their physicochemical characteristics is one of the key factors for evaluating underlying biological responses [ 3 , 4 ] and the biocompatibility of wear particles containing CoCrMo. The release of metallic particles and ions has been reported primarily for total hip arthroplasty (THA) and hip resurfacing (HR) implants with bearing components made of CoCrMo [ 5 7 ]. Arthroplasty registry studies of metal-on-metal and metal-on-polyethylene hip implants have indicated worse survival rates of some models, as compared to articular bearings made of alternative materials [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, understanding the reactivity of wear particles released from CoCrMo components in relation to their physicochemical characteristics is one of the key factors for evaluating underlying biological responses [ 3 , 4 ] and the biocompatibility of wear particles containing CoCrMo. The release of metallic particles and ions has been reported primarily for total hip arthroplasty (THA) and hip resurfacing (HR) implants with bearing components made of CoCrMo [ 5 7 ]. Arthroplasty registry studies of metal-on-metal and metal-on-polyethylene hip implants have indicated worse survival rates of some models, as compared to articular bearings made of alternative materials [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, polyethylene damage in a TKA may depend on gait characteristics [18] or the locking mechanism of the polyethylene insert in the metal tray [19]. Despite all the technological developments, the material characteristics of the implant play an important role [20].…”
Section: Introductionmentioning
confidence: 99%
“…This led some researchers to suggest production of materials that have heterogeneous and porous surface of the human cartilage, such as nano-hydroxyapatite-reinforced gel [ 4 ]. Poly vinyl alcohol (PVA) hydrogels, which is a long-chain hydrophilic polymer, have been proved to be effective after being used to replace the nucleus pulposus in spine surgery and in great toe implants for managing hallux rigidus and were suggested to have potential to be used in hip arthroplasty [ 43 ]. Self-healing materials with the ability to automatically repair themselves and to recover their function after being partially degraded or damaged might be seen in the future [ 44 ].…”
Section: Possible Future Innovationsmentioning
confidence: 99%